Influence of Seed Treatment on Seed Quality of Rice CMS Line Pusa 6A During Storage - PRAVEEN K SINGH; SHIV K YADAV; VILAS A TONAPI; AMIT BERA (Seed Research, 2026)
The present investigation was conducted to study the effect of seed treatments on storability of rice CMS line Pusa 6A. The seeds were coated with polymers: Disco Agro SP Blue (hydrophobic) and Disco Metal Red (hydrophilic) at different concentrations viz., one coat, two coats with and without thiram @2.5 g/kg seeds, thiram @ 2.5 g/kg seeds + thiamethoxam @2.5g/kg seed and neem oil @ 6ml/kg seed. The treated seeds were stored in three storage environments and evaluated for physiological quality attributes at three month intervals for a period of nine months. The seed quality declined with advancement in storage period, irrespective of storage environments and treatments. All the treatments showed significantly higher seed quality parameters compared to control, except neem oil and thiram + thiamethoxam. However, among the treatments, seed coated with polymer (hydrophobic and hydrophilic) @ 6 ml + thiram @ 2.5 g/kg seed revealed higher germination, vigour index, seedling length and dry weight, regardless of storage environments, until nine months of storage. Among the polymers, the hydrophobic polymer was more effective in maintaining the physiological quality of seed during the storage. The seeds stored in controlled environment at 15±2°C/35±5% RH showed better quality traits as compared to ambient environments, throughout the storage period. Therefore, hydrophobic polymer coupled with thiram can be used as treatment for storage of seeds of rice CMS line Pusa 6A, to maintain seed viability and vigour during 9 months of storage.